Demographic Decline in the Global South: Risks and Opportunities for Reform - Williams, Jonathan (International Higher Education, 2025)
Many jurisdictions in the so-called “Global South” have declining youth populations. This poses important risks for their higher education systems, including threatening academic integrity and institutional viability, especially in systems with many small institutions, as is the case in the four states of South India (Andhra Pradesh, Karnataka, Kerala, and Tamil Nadu). In such circumstances, policymakers should focus on system improvement and engaging in a deliberate process of strategic consolidation, rather than trying to keep small institutions open.